Cognate and false cognate processing by Brazilian speakers of Portuguese, English and French - Barcelos, Laura (2022)
Understanding how individuals who speak more than one language recognize and process words in different languages has been a central issue in multilingualism research. In recent decades, a great number of studies has gathered evidence demonstrating that the recognition of words in a language can be influenced by the knowledge of words in another language, that is, lexical access of multilingual individuals would be non-selective, meaning that both languages are active regardless of the target language. Thus, this study aimed at investigating the influence of the L1 and the L2 on the L3 in a group of 26 Portuguese (L1), English (L2) and French (L3) Brazilian trilinguals. Participants took part in two lexical decision tasks in French: the first composed of French words that were cognates with Portuguese, English or both, and the second included interlingual homographs in the same conditions. The results demonstrate the existence of an effect in the error percentages of both cognates and interlingual homographs, giving support to the non-selective lexical access hypothesis.